Public services in Ecuador: theoretical tensions between statism, liberalism and constitutional supremacy - Albuja Varela , Francisco Javier (2021)
This article identifies the theoretical tensions that come from the implementation of opposite economic constitutional models. These models can differ in nature: state-oriented (centralized planning) or favourable to economic liberalization and privatization. Public service theories, such as constitutional guarantees and mechanisms to satisfy general interest, were revised to find out whether the current Ecuadorian economic constitutional model enjoys legal flexibility to promote private management of public services. This article’s methodology applies an analytical and comparative approach to the economic model that shapes public services as stated both in the Ecuadorian Constitution of 1998 and that of 2008. This study concludes that the tensions between the economic models of public service provision can ease if the constitutional system adequately guarantees consumers’ freedom of choice rights and the freedom of the private sector to participate in the management of public services, including under privatization administrative techniques.